ADESÃO AS PRÁTICAS DE REPORTE AMBIENTAL DO DISTRITO AGROINDUSTRIAL DE ANÁPOLIS (CIPEEX, 2026)
The growing concern about climate change has pressured companies to adopt socio-environmental responsibility practices, using tools such as sustainability reports to communicate their commitments. This study aimed to evaluate the level of adherence of companies in the Agroindustrial District of Anápolis (DAIA) to the environmental reporting guidelines of the Global Reporting Initiative (GRI). The methodology consisted of a descriptive and documentary research, based on an official list of 154 active companies in the first half of 2024. Sustainability reports published in the last five years (2020-2024) were analyzed to verify the mention of operations in Anápolis and the use of a verifiable reporting methodology. The results indicate a low adherence, with only 8 companies, concentrated in the Chemical and Pharmaceutical, Textile and Apparel, and Packaging and Paper segments, publishing reports with local environmental indicators based on recognized standards. The Chemical and Pharmaceutical segment was the one that presented the highest volume of reports, with emphasis on the GRI 305 indicator (Emissions). It is concluded that there is a significant gap between the economic importance of DAIA and the maturity of its transparency practices, with the voluntary adoption of GRI guidelines still being incipient in the largest industrial hub of Goiás.
Keywords: Português